2009
DOI: 10.1111/j.1365-3148.2009.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus antibodies in blood donors from an endemic area

Abstract: SUMMARY.We evaluated the incidence of anti-Dengue virus (DENV) antibodies and dengue viremia in a region of Mexico with a high prevalence of dengue. DENV is the most important arthropod-borne virus in terms of human morbidity and mortality in America We tested 800 blood donors from a tertiary care teaching hospital that provides care in Northeast Mexico, to identify anti-DENV IgM and IgG antibodies by enzyme-linked immunosorbent assay (ELISA) and DENV genome by reverse transcription polymerase chain reaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…However, the true incidence of transfusion‐transmitted dengue is unknown because there is no surveillance for such events, and if a case is suspected, it is difficult to prove transfusion transmission (vs. vector‐borne transmission) in recipients from endemic countries. Nevertheless, transfusion risk models and assessments of viremia prevalence among blood donations indicate the potential for transfusion transmission of DENV in endemic areas 6‐8,11,12 . Risk is high in endemic areas as most DENV infections are asymptomatic and the viremia is high titered, long lasting, and detectable among asymptomatic individuals.…”
Section: Dengue Virus and Its Transmissionmentioning
confidence: 99%
“…However, the true incidence of transfusion‐transmitted dengue is unknown because there is no surveillance for such events, and if a case is suspected, it is difficult to prove transfusion transmission (vs. vector‐borne transmission) in recipients from endemic countries. Nevertheless, transfusion risk models and assessments of viremia prevalence among blood donations indicate the potential for transfusion transmission of DENV in endemic areas 6‐8,11,12 . Risk is high in endemic areas as most DENV infections are asymptomatic and the viremia is high titered, long lasting, and detectable among asymptomatic individuals.…”
Section: Dengue Virus and Its Transmissionmentioning
confidence: 99%
“…DENV infection is nationally notifiable in Mexico (Rojo-Medina, 2014), but the presence of subclinical infections and the lack of recent seroprevalence studies in blood donors have prevented an accurate estimation of risk of infection by DENV through blood transfusion (Grange et al, 2014). We previously reported that 2% of blood donors from Nuevo Leon state, an endemic area for dengue in Mexico, showed anti-DENV antibodies in 2007 (Rodríguez Rodríguez et al, 2009). Our objective was to assess whether the seroprevalence of anti-DENV antibodies remains constant in blood donors over time and compare it with routine serologic markers.…”
mentioning
confidence: 99%
“…[15] Moreover, none had clinical features of acute brucellosis or dengue fever, while only 2% of the overall samples were reactive for anti-dengue virus IgM antibodies. It is very unlikely that our patient and his mother both had brucellosis and dengue fever simultaneously.…”
Section: Discussionmentioning
confidence: 99%